Development experience of information system for ranking of academic and pedagogical staff - A. A. Chernousov; E. V. Vavilova (Открытое образование (Москва))
Purpose of research. The aim of this work is research of algorithms for quantitative assessment of intellectual potential (rating) of academic and pedagogical staff in higher educational institutions, as well as the development of technology for the application of these algorithms in practice.Materials and methods. According to the authors, the most appropriate method of assessing the diverse activities of the Faculty members is a technique based on the method of qualimetry – ranking objects in ascending or descending order based on the calculation of a certain set of features. This approach was embodied in the rules of rating of academic and pedagogical staff of Plekhanov Russian University of Economics. Due to the fact that the indicators can change annually the possibility of dynamic adjustment of indicators was provided in the project implementation. An important factor affecting design decisions is the need to process a large number of indicators in a limited time. At the same time, the preparation of data (their input and control, coordination) should be engaged in a large number of people who are employees of different departments, geographically distributed, in different subordination. In addition, it was necessary to take into account the possibility of new requirements for output forms. As a result, the concept of an automated rating system of Plekhanov Russian University of Economics was based on the following design decisions: dynamic setting of indicators and algorithms of ranking, the dynamic configuration of the personal account of the rated academic and pedagogical staff, external configuring of control parameters, the possibility of creating extensible libraries of output forms, the use of Internet technologies.Results. As a result of work the system of indicators of quantitative assessment, technology of their collecting and storage is prepared, and also the information system providing collecting, processing and display of the received results in an acceptable form on the basis of Internet technologies is realized. The technology of dynamic adjustment of the collected indicators, binding to the places of their formation, as well as setting the output forms has shown its effectiveness.Conclusion. Experience in the implementation of the rating system in Plekhanov Russian University of Economics showed that the independent automated assessment of the activity efficiency of officers allows to improve the mechanism of planning and personnel management system, allows to create model of stimulation of the types of activity influencing increase of the place of University in the Russian and international ratings, and also creates conditions for positive dynamics of growth of level of qualification of academic and pedagogical staff. At the same time, rating enables employees to identify areas for development and improvement, influence their earnings and receive competitive remuneration for their work. Implementation of rating system in Plekhanov Russian University of Economics proved the flexibility of the proposed approach, reduction of labor costs for data processing, full transparency of calculations, and, as a consequence, reduction of questions from the rated academic and pedagogical staff. In addition, the directions of technological development of the system are identified.